Comparison of Frailty Phenotypes for Prediction of Mortality, Incident Falls, and Hip Fracture in Older Women. Issue 9 (16th June 2016) - Zaslavsky, Oleg; Zelber‐Sagi, Shira; Gray, Shelly L.; LaCroix, Andrea Z.; Brunner, Robert L.; Wallace, Robert B.; O'Sullivan, Mary J.; Cochrane, Barbara; Woods, Nancy F.
Abstract : Objectives: To compare the ability of the commonly used Women's Health Initiative (WHI) and Cardiovascular Health Study (CHS) frailty phenotypes to predict falls, hip fracture, and death in WHI Clinical Trial participants aged 65 and older. Design: Longitudinal cohort study. Setting: WHI Clinical Trial. Participants: Participants with data for WHI and CHS frailty phenotypes (N = 3, 558). Measurements: Frailty was operationally defined in the CHS as the presence of three or more of weight loss, poor energy, weakness, slowness, and low physical activity. WHI operationalized frailty similarly but with the RAND‐36 physical function scale substituted for slowness and weakness (RAND‐36 physical function scale score <13 = 2 points, 13–78 = 1 point, >78 = 0 points). Frailty was defined as a summary score of 3 or greater, prefrailty as a score of 2 or 1, and nonfrailty as a score of 0. Outcomes were modeled using Cox regression. Harrell C‐statistics were compared for models containing alternative instruments. Results: Approximately 5% of participants were frail based on the CHS or WHI phenotype. The WHI frailty phenotype was associated with higher rates of falls (hazard ratio (HR) = 1.48, P = .003), hip fracture (HR = 1.87, P = .04), and death (HR = 2.32, P < .001). Comparable HRs in CHS‐phenotype frail women were 1.32 ( P = .04), 1.08 ( P = .83), and 1.91 ( P < .001), respectively. Harrell C‐statistics revealed marked but insignificant differences in predicting abilities between CHS and WHI phenotype models ( P > .50 for all). Conclusion: The WHI phenotype, which does not require direct measurements of physical performance, might offer a practical advantage for epidemiological and clinical needs.